(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This empirical study explores the socio-cultural dynamics and development perceptions among Khmer community in Tra Vinh, Vietnam, based on survey data collected from respondents across two districts in one year. The research investigates six key domains: perceptions of current living conditions; continuity and change in traditional cultural practices; drivers of community participation; engagement with Khmer-language media; attitudes toward cultural preservation initiatives; and community-defined priorities for government support. Findings indicate a generally optimistic outlook across these dimensions, with high levels of self-initiated civic engagement, consistent media consumption in the Khmer language, and broad approval of cultural preservation efforts. Respondents emphasized employment generation and poverty alleviation as top government priorities, highlighting the intersection of material needs and cultural sustainability. The study underscores the value of integrating cultural identity into development planning and emphasizes the role of community agency in shaping locally meaningful progress.